Pola Sebaran Klorofil-a dan Kualitas Air Pada Kawasan Budidaya Rumput Laut Di Perairan Pulau Semau Kabupaten Kupang - Yusuf Kamlasi; Sri Rejeki; Slamet Budi Prayitno; Frida Purwanti (Jurnal Kelautan Tropis, 2024)
Seaweed cultivation area is habitat and development if the ecological conditions of the waters support the growth and survival of seaweed. Chlorophyll is one of the parameters that greatly determines primary productivity in the sea. The study aims to find out the patterns of chlorophyll-a spread and water quality in seaweed cultivation areas. The methods used in the investigation were the survey method for water sampling in the field and the spectrophotometry method for laboratory analysis. The results of the survey showed that the chlorophyll value in the seaweed cultivation area in October 2023 averaged 1.43 mg/m3, while in December 2023 the average chlorophyll-A level was 0.90 mg/m3. The chlorophyll-a content in the waters of the island of Semau in October 2023 ranged between 0.29 and 4.56 mg/m3, while in December 2023 it ranged between 0.09 and 2.82 mg/m3. Water quality parameters that affect chlorophyll distribution include nitrates, temperature, salinity, brightness, depth, dissolved oxygen, and pH.